The role of organic matter on the adsorption of mercury in sediments from Amazon lakes, Brazil - Bonotto, Daniel Marcos [UNESP]; Vergotti, Marcelo; Da Silveira, Ene Gloria (Int Assoc Hydrological Sciences, 2006)
Gold has been exploited intensively in the Brazilian Amazon during the past 20 years, and the elemental mercury (Hg) used in amalgamating the gold has caused abnormal Hg concentrations in waterways. Since 1986 particular attention has been given to the Madeira River because it is the largest tributary of the Amazon River and gold mining was officially allowed on a 350-km sector of the river. In this paper, samples of sediments from nine lakes located in the Madeira River basin, Rondonia State, Brazil, were analysed for mercury and organic matter. The average Hg content ranged between 33 and 157 ppb, which is about 8-40 times higher than the average value corresponding to 4.4 ppb for rocks occurring in the area (regional background). Significant correlation was found between the Hg content and organic matter in the sediments, indicating its importance on the retention of this heavy metal.
Keywords: amazon lakes; Madeira River basin; mercury; organic matter; physical weathering; sediments